The Relationship Between the Duration of Kangaroo Mother Care and Edinburgh Postnatal Depression Scale Outcomes in Mothers with Preterm Infants - Pranoto, Ivena Celia Eileen; Suswihardhyono, Adhie Nur Radityo; Wardani, Natalia Dewi (Faculty of Medicine, Universitas Diponegoro, 2024)
Background: Preterm birth has a negative impact on the health of the baby and increases the risk of postpartum depression in mothers. Kangaroo mother care (KMC) is a preterm baby care which is considered to increase bonding between mother and baby, thereby reducing the incidence of postpartum depression, which can be evaluated using the Edinburgh Postnatal Depression Scale (EPDS) instrument.Objective: To find out the relationship between the duration of KMC and EPDS outcomes in mothers with preterm infants.Methods: This study used a quasi-experimental method with non-randomized control group pre-test and post-test design and was conducted on 34 mothers with preterm infants who gave birth at Dr. Kariadi Hospital Semarang. The research subjects were selected using consecutive sampling method and were asked to perform kangaroo mother care for 60 minutes daily (control group) and 120 minutes daily (treatment group) for 14 days. Evaluation was carried out using the Edinburgh Postnatal Depression Scale questionnaire, which was completed twice, as a pre-test and post-test. Data analysis was performed using paired sample T-test and independent samples T-test to determine the relationship between variables.Results: Results showed that there was a significant relationship between the duration of KMC and EPDS outcomes. The difference between the decreased of EPDS scores in the control and treatment groups was significant (p=0.017). The significant decrease of EPDS score was found in the treatment group (p<0.001). The decrease of EPDS score in the control group was not significant (p=0.704).Conclusion: Increasing duration of KMC lowers the score of EPDS in mothers with preterm infants.